On this page we discuss how to eliminate the parameter from parametric equations.
Recommended Books on Amazon (affiliate links)  

Topics You Need To Understand For This Page 

Related Topics and Links 
Eliminating The Parameter
Sometimes we are given the set of parametric equations and we are asked to write the equation without the parameter by eliminating the parameter. This not always possible but with some equations there are ways to do it. Here are some of the ways.
Solve For \(t\) and Substitute
The easiest technique to try is to solve one of the equations for the parameter and then substitute the result in the other equation. Here is an example.
\( x = 2t \) and \( y = t^2 \)
Solve the first equation for \(t\) giving \( t=x/2\) and substitute into the second equation.
\( y = (x/2)^2 = x^2/4 \)
WARNING  This technique can sometimes lead to errors if you are not careful. One example is shown below in practice problem 4423. You need to be careful to watch that you do not lose information about the domain and range when you perform algebra.
For example, if you have \(x=\sqrt{t}\) and you square both sides to get \(x^2=t\). Now, even though you have performed a valid operation, these equations are NOT the same. In the first one, \(x\) and \(t\) are both greater than or equal to zero. However, in the second one, \(x\) can be negative. So certain operations require you to keep the domain (when working with \(x\)) and the range (when working with \(y\)) in mind.
Here are some situations you need to watch out for.
1. when you taking the even power or even root of both sides of an equation,
2. when you are working with trig functions and taking inverses
3. when you are working with logarithms
4. when you dividing by a term, make sure it is never zero
Use Trig Identities
A second technique involves the use of trig identities. For example, given the parametric equations \( x=\cos(t)\) and \(y=\sin(t)\), we know that \( \cos^2(x) + \sin^2(x) = 1 \). So we can write \( x^2 + y^2 = 1 \) which eliminates the parameter.
By Inspection
A third way is by inspection.
Sometimes it is obvious what a substitution might be.
For example, if we have \(x=e^t\) and \(y=e^{3t}+1\) then we can rewrite \(y=(e^t)^3+1\).
Then we can replace \(e^t\) with \(x\) in the last equation (because our first parametric equation was \(x=e^t\)) to get \(y=x^3+1\).
Of course, the first technique would have worked too by solving \(x=e^t\) for \(t\) and then substituting and simplifying but by standing back and looking at the equations more carefully, the solution was much easier.
Okay, time for some practice problems.
Practice
Unless otherwise instructed, eliminate the parameter from these parametric equations. State restrictions on the domain and range, if any exist.
Eliminate the parameter \(t\) from \(x=3t\) and \(y=t^2\).
Problem Statement 

Eliminate the parameter \(t\) from \(x=3t\) and \(y=t^2\).
Final Answer 

\( y = x^2/9 \)
Problem Statement
Eliminate the parameter \(t\) from \(x=3t\) and \(y=t^2\).
Solution
Solve the first equation for t giving \(t=x/3\) and substitute into the second equation.
\( y = (x/3)^2 = x^2/9 \)
Final Answer
\( y = x^2/9 \)
Log in to rate this practice problem and to see it's current rating. 

\(x=\sqrt{t}\), \(y=1t\)
Problem Statement 

Eliminate the parameter from the parametric equations \(x=\sqrt{t}\), \(y=1t\)
Final Answer 

\(y = 1x^2\), \(x \geq 0\)
Problem Statement
Eliminate the parameter from the parametric equations \(x=\sqrt{t}\), \(y=1t\)
Solution
Here is one of the times you need to be careful about domain. In the video, he squares both sides of \(x=\sqrt{t}\) but doesn't mention that doing so requires you to be careful about the domain. In this case, the correct answer requires you to say that \(x \geq 0\)
video by PatrickJMT 

Final Answer
\(y = 1x^2\), \(x \geq 0\)
Log in to rate this practice problem and to see it's current rating. 

Eliminate the parameter \(t\) from \(x=3\cos(t)\) and \(y=2\sin(t)\).
Problem Statement 

Eliminate the parameter \(t\) from \(x=3\cos(t)\) and \(y=2\sin(t)\).
Final Answer 

\(\displaystyle{ \frac{x^2}{9} + \frac{y^2}{4} = 1 }\)
Problem Statement
Eliminate the parameter \(t\) from \(x=3\cos(t)\) and \(y=2\sin(t)\).
Solution
We will use the trig identity \( \cos^2(t) + \sin^2(t) = 1 \).
\( x = 3\cos(t) \to x/3 = \cos(t) \)
\( y = 2\sin(t) \to y/2 = \sin(t) \)
\( (x/3)^2 + (y/2)^2 = 1 \)
Final Answer
\(\displaystyle{ \frac{x^2}{9} + \frac{y^2}{4} = 1 }\)
Log in to rate this practice problem and to see it's current rating. 

Eliminate the parameter t from \(x=5\cos(t)\) and \(y=3\sin(t)\).
Problem Statement 

Eliminate the parameter t from \(x=5\cos(t)\) and \(y=3\sin(t)\).
Final Answer 

\( 9x^2 + 25y^2 = 225 \)
Problem Statement
Eliminate the parameter t from \(x=5\cos(t)\) and \(y=3\sin(t)\).
Solution
In the video, she shows a really difficult way to solve this problem. Her solution is correct but it is overly tedious and unnecessarily complicated. Here is an easier and more common solution.
In this problem, you are given that \(x=5\cos(t)\) and \(y=3\sin(t)\). We solve each of these for the sine and cosine terms since we use \(\cos^2(t)+\sin^2(t)=1\). So we have \(x/5=\cos(t) \to (x/5)^2=\cos^2(t)\) and \(y/3=\sin(t) \to (y/3)^2=\sin^2(t)\).
\(\begin{array}{rcl} 1 & = & \cos^2(t)+\sin^2(t) \\ 1 & = & (x/5)^2+(y/3)^2 \\ 1 & = & x^2/25+y^2/9 \\ 225 & = & 9x^2 + 25y^2 \end{array}\)
video by Krista King Math 

Final Answer
\( 9x^2 + 25y^2 = 225 \)
Log in to rate this practice problem and to see it's current rating. 

Eliminate the parameter from the parametric equations \(x=t1\), \(y=4t+1\).
Problem Statement
Eliminate the parameter from the parametric equations \(x=t1\), \(y=4t+1\).
Solution
video by PatrickJMT 

Log in to rate this practice problem and to see it's current rating. 

Eliminate the parameter from the parametric equations \(x=\sqrt{t+1}\), \(y=3t+2\).
Problem Statement
Eliminate the parameter from the parametric equations \(x=\sqrt{t+1}\), \(y=3t+2\).
Solution
video by PatrickJMT 

Log in to rate this practice problem and to see it's current rating. 

Eliminate the parameter t from \( x=\ln t \) and \( y=\sqrt{t} \).
Problem Statement
Eliminate the parameter t from \( x=\ln t \) and \( y=\sqrt{t} \).
Solution
video by Michel vanBiezen 

Log in to rate this practice problem and to see it's current rating. 

Eliminate the parameter \(t\) from \( x=e^t1 \) and \( y=e^{2t} \).
Problem Statement 

Eliminate the parameter \(t\) from \( x=e^t1 \) and \( y=e^{2t} \).
Final Answer 

\( y=x^2+2x+1 \)
Problem Statement
Eliminate the parameter \(t\) from \( x=e^t1 \) and \( y=e^{2t} \).
Solution
video by Michel vanBiezen 

Final Answer
\( y=x^2+2x+1 \)
Log in to rate this practice problem and to see it's current rating. 

Eliminate the parameter from the parametric equations \(x=4e^{t/4}\), \(y=3e^t\).
Problem Statement
Eliminate the parameter from the parametric equations \(x=4e^{t/4}\), \(y=3e^t\).
Solution
video by PatrickJMT 

Log in to rate this practice problem and to see it's current rating. 

Really UNDERSTAND Calculus
Log in to rate this page and to see it's current rating.
To bookmark this page and practice problems, log in to your account or set up a free account.
Do you have a practice problem number but do not know on which page it is found? If so, enter the number below and click 'page' to go to the page on which it is found or click 'practice' to be taken to the practice problem.
 
free ideas to save on books 

Join Amazon Prime  Watch Thousands of Movies & TV Shows Anytime  Start Free Trial Now 
I recently started a Patreon account to help defray the expenses associated with this site. To keep this site free, please consider supporting me. 

Support 17Calculus on Patreon 

